The relationship between flavor formation, lipid metabolism, and microorganisms in fermented fish products. Issue 13 (25th May 2021) - Feng, Lin; Tang, Nianchu; Liu, Ruijie; Gong, Mengyue; Wang, Zhangtie; Guo, Yiwen; Wang, Yandan; Zhang, Yao; Chang, Ming
Abstract : This manuscript clarifies the relationship between flavor formation, lipid metabolism, and microorganisms in fermented fish products. Abstract : Traditional fermented fish products are favored due to their unique flavors. The fermentation process of fish is accompanied by the formation of flavor substances through a complex metabolic reaction of microorganisms, especially lipolysis and lipid oxidation. However, it is difficult to precisely control the reaction of microorganisms during the fermentation process in modern industrial production, and fermented fish products have lost their traditional characteristic flavors. The purpose of this review is to summarize the different kinds of fermented fish, core microorganisms in it, and flavor formation mechanisms, providing guidance for industrial cultural starters. Future research on the flavor formation mechanism is necessary to confirm the relationship between flavor formation, lipid metabolism, and microorganisms to ensure stable flavor and safety, and to elucidate the mechanism directly toward industrial application.